EVALUATION OF POTATO CULTIVARS AND LINES FOR FROST TOLERANCE - Kang, G. S.; Kumar, Raj; Pandey, S. K. (Potato Journal, 2013)
Evaluation of 98 lines/cultivars for frost tolerance under natural conditions showed that CP 1619, CP 2318, A.98-166, A.98-54, J.95-229 and JX 576 suffered less than 10% foliage damage due to frost. Among the cultivars evaluated for frost tolerance Kufri Pushkar was the best with foliage damage of about 30%.